Renal hemorrhagic actinomycotic abscess in pregnancy - Marcela C. Smid; Neha R. Bhardwaj; Laura M. Di Giovanni; Scott Eggener; Micaela Della Torre (MDPI AG, 2014)
Actinomyces israelii is a gram-positive, filamentous anaerobic bacteria colonizing the oral and gastrointestinal tracts. Retroperitoneal actinomycotic abscess is uncommon and its rare presentation as a hemorrhagic mass may be confused with malignancy. We present a case of this unusual infection complicating pregnancy. Increased awareness of actinomycotic abscess in the differential diagnosis of renal mass concerning for malignancy is critical to early recognition and treatment of this rare infection and most importantly, avoidance of unnecessary surgical intervention.